ANALISIS METODE REALIS PADA PEMBELAJARAN SENI PERAN UNTUK MENINGKATKAN KECERDASAN KINESTETIK DI SMPN 1 KARANGNUNGGAL - Aldi Ernawan; Arni Apriani; Wan Ridwan Husen (Magelaran: Jurnal Pendidikan Seni, 2021)
The title that the researcher adopted inthis study was about the development of role art learning to improve kinesthetic intelligece in class viii junior high school 1 Karangnunggal. The problem behind this problem is that it is often difficult for class VIII students to play roles, and to function their bodies (physically) as well as creative and innovative ideas. Researchers see how important it is to improve kinesthetic intelligence through learning the art of acting. Because this learning can iincrease body flexibility and body response and can develop ideas in acting. Students can also learn more confidently and also be fun in this lesson so that the atmosphere in the classroom is not saturating. The sampel of this researcher is 1 class from class VIII. The application of the realisst methode of Stanilafski is a method of percentage acting that prioritizes identification between the actor and the character’s soul, so that the transformation process will develop to find its target. Learning methods that will be applied by meas of interviews, observation, and documentation so that it is easy to interact with students. In addition, the method that the author applies in this study is closely related to increasing kinesthetic intelligence. Acting is someone who becomes or incarnates another according to the script that is delivered, so that events on stage can be seen as real. But the problem in applying the realist method is that students lack knowledge of acting so that students do not know the strengths is their body or physicality. In addition to students not knowing the role of art, the facility also interferes with the learning process of applying the realist method which aims to improve kinesthetic intelligence. Researchers want the results of this research, studet researchers can know or recognize their bodies, and the meaning or meaning of acting along with realist methods. Kinesthetic intelligence is an idea formation as well as physical development. The method used is qualitative with a descriptive analysis approach. Da obtained by means of interviews, documentation an drawing conclusions.